2019
DOI: 10.5696/2156-9614-9.23.190908
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cassava Peel Extracts for the Removal of Heavy Metals from Hospital Sewage Sludge in Nigeria

Abstract: Background. The use of strain-specific microbial fermentation in the production of organic acids for the removal of heavy metals from sludge has been extensively studied. However, there is scarce information on the use of microflora for fermentation. Objectives. To assess the efficacy of cassava peel extracts for the removal of heavy metals from hospital sewage sludge in Nigeria. Methods. A composite sewage sludge sample was collected from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For example, cassava tubers supply ~70% of the daily calorie input for >50 million people in Nigeria, the world’s largest cassava producer (49 million metric tons/year). Fresh cassava root contains >30% carbohydrate, >2% protein, 0.1% fat, and >75% moisture content [ 82 , 83 ]. However, M. esculenta also synthesizes cyanogenic glucosides (linamarin and its methylated relative lotaustralin; 97:3), the concentration of which must be substantially reduced before the tuber is used for human consumption.…”
Section: Heavy Metals In Plants With Potential Neurotoxicitymentioning
confidence: 99%
“…For example, cassava tubers supply ~70% of the daily calorie input for >50 million people in Nigeria, the world’s largest cassava producer (49 million metric tons/year). Fresh cassava root contains >30% carbohydrate, >2% protein, 0.1% fat, and >75% moisture content [ 82 , 83 ]. However, M. esculenta also synthesizes cyanogenic glucosides (linamarin and its methylated relative lotaustralin; 97:3), the concentration of which must be substantially reduced before the tuber is used for human consumption.…”
Section: Heavy Metals In Plants With Potential Neurotoxicitymentioning
confidence: 99%
“…After centrifugation at 1,000 rpm for 1 hour, the heavy metal concentrations of treated samples were analyzed and compared to control samples. It was found that the Aspergillus niger treatment resulted in concentrations of zinc, copper, chromium, nickel, and lead that were all below permissible limits, indicating that cassava peel extract may be used as an alternative method to remove heavy metals from wastewater sludge (Adeolu & Adewoye, 2019). Bogusz and Oleszczuk (2020) concluded that Cd and Cu were more mobile in control soil when compared to wastewater sludge-treated and biochar-treated soil.…”
Section: Metalsmentioning
confidence: 99%
“…Adeolu and Adewoye (2019) conducted a study to assess the use of microflora to remove heavy metals from wastewater sludge generated by a Nigeria hospital. Cassava peels were used to obtain Aspergillus niger fermentation extract, and 10ml of the extract was added to 3g of wastewater sludge sample.…”
Section: Analysis and Quantification Of Characteristicsmentioning
confidence: 99%
“…In addition, cassava starch granules consist of amylose (20%) and amylopectin (80%) [14]. Therefore, the sludge produced from the coagulation process by vegetable coagulants, including cassava, is cost-effective, highly biodegradable, non-toxic, non-corrosive and unlikely to produce air with extreme pH [15]. In addition, natural coagulants are relatively inexpensive to obtain and are available locally.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to view a co-word map or keyword map on research developments in a specific field of science is through density visualization [15]. Figure 3 depicts a high-level overview of keyword density in cassava peel research.…”
Section: Introductionmentioning
confidence: 99%